Grammatical Error Analysis on Analytical Exposition Text Made by the Eleventh Grade Students of SMAN 1 Porong - Anita Maghfiroh; Sulistyaningsih Sulistyaningsih (P-SEMART JOURNAL, 2022)
This research aimed to find out the common types of errors committed by the eleventh grades students of SMAN 1 Porong. Theoretically, this research intended to identify, classify, and explain the types of errors made by the students. In addition, this research aimed to find out the highest frequency of errors that had been found on analytical exposition written text made by the students. The method utilized in this research was descriptive qualitative research. The subject was 15 students of the eleventh grades students in SMAN 1 Porong. The data were collected by instructing the students to write analytical exposition text. The errors were classified using the theoretical of Dulay’s surface strategy taxonomy including omission, addition, misformation, and misordering. By analyzing the students’ analytical exposition written text, the total number of errors was 85 errors. The students committed error in all types: 30 omissions (35%), 21 addition (25%), 22 misformation (26%), and 12 misordering (14%). Hence, the highest frequency of errors on students’ analytical exposition written text is omission with 30 errors (35%). The frequency of students’ error happened because the students did not know well about the grammar or English structure rules that should be used in a sentence. Based on the findings and discussions of the result, the conclusion was many students still faced difficulties in the English structure rules. Due to the result of this research, the students needed to learn more about grammar to enhance their knowledge and decrease their errors in writing.